Measurement Tool for The Adoption of ChatGPT in Educational Institutions in Botswana - Letjani, Kutlo; Indrawati, Indrawati; Widiyanesti, Sri (ADPEBI, 2024)
ChatGPT helps users to write, learn, and even do assessments with the help of artificial intelligence in the form of a chatbot. Education is therefore receiving much attention in Botswana for economical and social development to be realized. In Botswana, the late implementation of ChatGPT has been associated with a lack of awareness. According to a survey, 55 % of university students use ChatGPT while 22% use it for academic purposes. Although, the study reveals that out of the students, 89 % have incorporated ChatGPT in a class environment. It is for this reason that there is comparatively limited research on this phenomenon within less developed and emerging countries like Botswana. As a result, this research aims to comprehensively understand and analyze the factors influencing customer adoption of ChatGPT within educational institutions in Botswana. SmartPLS for structural equation modeling was employed where through purposive sampling the target was 30 respondents who used ChatGPT in their academic settings. As a result the pilot test showed that the tool was valid and reliable, and consists of 10 variables and 36 items, and could be applied for further studies.